A model for real-time recognition and textual representation of Malaysian sign language through image processing - Karabasi, Mostafa; Bhatti, Zeeshan; Shah, Asadullah (2013)

(untitled)
In this paper we discuss a stand-alone system to allow the deaf or hard-of-hearing people and normal people to communicate with each other easily and fluently. We propose a model for recognizing Malaysian sign language through image processing techniques and converting the visual information into textual information in real-time. In order to implement a real time hand gesture recognition system, video footage will be obtained from digital camera or cellphone camera, then hand position and location will be marked and cropping will be done to isolate them. Then the hand gestures will be recognized through image processing and matched to a pre-built database of gestures which will be used for textual conversion on the screen. In the final step the normal person will types the text and its equivalent animation of hand gesture will be presented. Through this system, real-time recognition of Malaysian sign language and textual representation is done, giving more accurate results at least possible time. It will not only benefit the deaf and dumb people of Malaysia but also could be used in various applications in the technology filed. This system provides the flexibility to learn Malaysian Sign Language at personal pace, at any time and any where at home or at workplace.